Relationships between flowering behavior and seed yield in mungbean mutants - Mondal, M M A; Sen, A (Bangladesh Journal of Nuclear Agriculture, 2024)
Flower is the prime sink that produces pods and yield depends on numbers and size of pods in legume crops. Flowering behavior affects the synchrony of pod maturity, which is crucial for efficient harvesing that regulates the yield. Thus, it is essential to study the relationship between flowering behavior and pod yield in mungbean mutants. This experiment was conducted using a Randomized Complete Block Design (RCBD) with three replications at the BINA headquarters physiology pot yard. The aim was to assess the relationship between flowering patterns, flowering duration, and seed yield in ten mungbean mutants/varieties. Results indicated that high-yielding mutant (MM-1) produced more opened flowers (38.0 flowers per plant) and had a longer flowering duration (12 days) compared to low-yielding varieties/mutants (13.1-18.0 flowers per plant and 7-9 days). Additionally, high-yielding varieties exhibited higher flower production rates over time, with peak flower production occurring within 5-8 days, while low-yielding varieties peaked within 3-4 days. High-yielding mungbean mutants/varieties exhibit lower pod set and reproductive efficiency (48.7-55.0%) compared to low-yielding ones (63.2-70.9%), indicating potential for yield improvement in high-yielding genotypes through enhanced pod set. Pod number, a key yield parameter, has a significant positive correlation with flower number (r = 0.56**), while pod number is also dependent on flowers per plant (r = 0.68**). Additionally, seed yield shows a strong positive relationship with the harvest index (r = 0.62**). These findings suggest that future breeding efforts should focus on synchronizing flower production to increase mungbean yield. Bangladesh J. Nuclear Agric, 38(1): 111-117, 2024